Cognitive–emotional hyperarousal in the offspring of parents vulnerable to insomnia: a nuclear family study. (30th May 2014) - Fernandez‐Mendoza, Julio; Shaffer, Michele L.; Olavarrieta‐Bernardino, Sara; Vgontzas, Alexandros N.; Calhoun, Susan L.; Bixler, Edward O.; Vela‐Bueno, Antonio
Summary Cognitive–emotional hyperarousal is believed to be a predisposing factor for insomnia; however, there is limited information on the association of familial vulnerability to insomnia and cognitive–emotional hyperarousal. The aim of this study was to estimate the heritability of stress‐related insomnia and examine whether parental vulnerability to stress‐related insomnia is associated with cognitive–emotional hyperarousal in their offspring. We studied a volunteer sample of 135 nuclear families comprised of 270 middle‐aged (51.5 ± 5.4 years) fathers and mothers and one of their biological offspring (n = 135, 20.2 ± 1.1 years). We measured vulnerability to stress‐related insomnia (i.e. Ford Insomnia Response to Stress Test: FIRST), perceived stress, depression and anxiety in all participants, and arousability, presleep cognitive and somatic arousal, coping and personality in the offspring. We found a heritability estimate of 29% for FIRST scores. High FIRST parents had three to seven times the odds of having offspring highly vulnerable to stress‐related insomnia. Offspring of high FIRST parents showed higher arousability, presleep cognitive arousal and emotion‐oriented coping. Furthermore, high FIRST mothers contributed to offspring's higher anxiety and lower task‐oriented coping, while high FIRST fathers contributed to offspring's higher presleep somatic arousal and conscientiousness. Vulnerability to stress‐related insomnia is significantly heritable. Parents vulnerable to stress‐related insomnia have offspring with cognitive–emotional hyperarousal who rely upon emotion‐oriented coping. These data give support to the notion that arousability and maladaptive coping are key factors in the aetiology of insomnia.